A Critical Analysis of Fundamental Rights Under the Constitution of Pakistan, 1973 - Dr. Naveed Ahmed (Journal of Political Studies, 2021)
In general sense the right is considered that source by using that a person is being entitled for all obligation intended to other persons as per the approved limitation of law. The legal right after its recognition takes power for its enforceability from the Constitution. Therefore, in order to alter a legal right, it needs amendments in the Constitution by legislature. The philosophy of human rights is as old as the establishment of mankind. The right to life is considered as the most important and basic human right and is the foundation of all other rights guaranteed by the Constitution. However, where there is right there is always some obligation to enjoy that right. The right of equality demands that all the people have same rights and self-respect as they are born as free and entitle for equal protection as per the Constitution without any discrimination. Generally, human rights are deliberated as a matter of right other than special favor and privilege and must be accepted with full regard not being constrained to the territorial limitations. Therefore, the focus of this study is to critically analyze the most important fundamental rights and how seriously the judiciary of Pakistan perceives these rights in the context of Constitution of Pakistan, 1973. The study may provide an opportunity to build a bridge between the judiciary and the executive for the proper implementation of fundamental rights in Pakistan.